Accommodation and Negotiation with Context‐Sensitive Expressions. (11th May 2014) - Silk, Alex
<x xml:space="preserve">Abstract</x> Contextualists and relativists about predicates of personal taste, epistemic modals, and so on ("CR‐expressions") agree that the interpretation of these expressions depends, in some sense, on context. Relativists claim that the sort of context‐sensitivity exhibited by CR‐expressions is importantly different from that exhibited by paradigm context‐sensitive expressions. This bifurcation is often motivated by the claim that the two classes of expressions behave differently in patterns of agreement and disagreement. I provide cases illustrating that the same sorts of discourse phenomena that have been thought problematic for contextualists can arise with paradigm context‐sensitive expressions. These cases motivate a more unified treatment of paradigm context‐sensitive expressions and the expressions that have figured in recent contextualism/relativism debates.